2017
DOI: 10.1021/acs.iecr.7b04641
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Photocatalytic Applications of Perovskite Materials with Special Emphasis on Alkali-Metal-Based Niobates and Tantalates

Abstract: Population explosion has caused serious environmental and energy-related problems that have increased the interest of researchers to develop new nontoxic, inexpensive, stable, and efficient materials to address these environment and energy-related issues. Among the different efforts, the development of photocatalysts is considered as an important way to utilize the sustainable solar energy for environment remediation and energy purposes. Presently, several hundred photocatalysts have been synthesized. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 181 publications
0
44
0
Order By: Relevance
“…Interestingly, the Nd 0.3 Sr 0.7 MnO 3 content has the highest degradation rate of AO which is two times faster than undoped NdMnO 3 . This superior behavior in photocatalytic activity of Nd 0.3 Sr 0.7 MnO 3 nanocomposite emerges from large surface area, structural anisotropy, and small particle size 56 . As shown in XRD findings, the phase crystalline NdMnO 3 nanocomposite is monoclinic and orthorhombic crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the Nd 0.3 Sr 0.7 MnO 3 content has the highest degradation rate of AO which is two times faster than undoped NdMnO 3 . This superior behavior in photocatalytic activity of Nd 0.3 Sr 0.7 MnO 3 nanocomposite emerges from large surface area, structural anisotropy, and small particle size 56 . As shown in XRD findings, the phase crystalline NdMnO 3 nanocomposite is monoclinic and orthorhombic crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the achievements of Kudo and co‐workers, a large number of studies have since been conducted to develop NaTaO 3 ‐based photocatalysts that are efficient for artificial photosynthesis, with more than 180 studies, as well as reviews, reported to date . Doping with lanthanoid cations, not limited to La 3+ , and alkaline‐earth metal cations improved the water splitting efficiency (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…1114 Later, different metal oxide nanoparticles like niobates and tantalates were explored for their photocatalytic activity in water splitting and removal of organic contaminants from water. 15,16 NaTaO 3 , being an important member of tantalate perovskites, has been explored extensively for its photocatalytic water splitting activity due to its stability and structural flexibility. In the NaTaO 3 structure, the corner sharing of TaO 6 octahedron forms a three-dimensional structure with sodium ions at dodecahedral interspaces, which maintains the stability of the NaTaO 3 structure.…”
Section: Introductionmentioning
confidence: 99%